To evaluate disparity between clinical and pathological tumor-node-metastasis staging in oral cavity squamous cell carcinoma patients and its impact on overall survival: An institutional study - Gupta, Karan (South Asian J Cancer, 2015)
BACKGROUND: Accurate clinical staging is important for patient counseling, treatment planning, prognostication, and rational design of clinical trials. In head and neck squamous cell carcinoma, discrepancy between clinical and pathological staging has been reported. OBJECTIVE: To evaluate any disparity between clinical and pathological tumor-node-metastasis (TNM) staging in oral cavity squamous cell carcinoma (OCSCC) patients and any impact of the same on survival. MATERIALS AND METHODS: Retrospective chart review from year 2007 to 2013, at a tertiary care center. STATISTICAL ANALYSIS: All survival analyses were performed using SPSS for Windows version 15 (Chicago, IL, USA). Disease-free survival curves were generated using Kaplan–Meier algorithm. RESULTS: One hundred and twenty-seven patients with OCSCC were analyzed. Seventy-nine (62.2%) were males and 48 (37.8%) females with a mean age at presentation 43.6 years (29–79 years). The highest congruence between clinical and pathological T-staging seen for clinical stage T1 and T4 at 76.9% and 73.4% with pathological T-stage. Similarly, the highest congruence between clinical and pathological N-stage seen for clinical N0 and N3 at 86.4% and 91.7% with pathological N-stage. Of clinically early stage patients, 67.5% remained early stage, and 32.5% were upstaged to advanced stage following pathological analysis. Of the clinically advanced stage patients, 75% remained advanced, and 25% were pathologically downstaged. This staging discrepancy did not significantly alter the survival. CONCLUSION: Some disparity exists in clinical and pathological TNM staging of OCSCC, which could affect treatment planning and survival of patients. Hence, more unified and even system of staging for the disease is required for proper decision-making.